2020
DOI: 10.1016/j.xphs.2019.10.053
|View full text |Cite
|
Sign up to set email alerts
|

Development of Freeze-Drying Cycles for Pharmaceutical Products Using a Micro Freeze-Dryer

Abstract: This article aims to investigate how a small-scale freeze-dryer can be used for process design. The system encompasses a temperature controlled metallic ring that surrounds a small batch of vials, in contact with the external vials through removable thermal conductors. The temperature of the ring can be modified to keep a constant difference with the temperature of one or more vials of the batch. In this article, an extensive validation of the system is given, considering 10% w/w sucrose and 5% w/w mannitol so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The resulting K v found in that study was 16.7 ± 2.3 W/m 2 K (33). In this present study, the non-gravimetric K v estimation resulted in 16.2 ± 1.8 W/m 2 K. For the MicroFD®, using the −5°C offset setting for the LyoSim®, K v values in the MicroFD® were found correspondent to REVO® central batch ones (35). The observed R p values found in this study were also in good agreement with previously reported values (18,28).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The resulting K v found in that study was 16.7 ± 2.3 W/m 2 K (33). In this present study, the non-gravimetric K v estimation resulted in 16.2 ± 1.8 W/m 2 K. For the MicroFD®, using the −5°C offset setting for the LyoSim®, K v values in the MicroFD® were found correspondent to REVO® central batch ones (35). The observed R p values found in this study were also in good agreement with previously reported values (18,28).…”
Section: Discussionsupporting
confidence: 59%
“…The use of the MicroFD® with a LyoSim® offset temperature of −5°C with respect to the product temperature resulted in good batch homogeneity (46). Moreover, this offset setting was found to be a good emulator of central batch conditions in the REVO® freeze-dryer (35). This −5°C setting was also found to represent well the temperature profiles and K v values of central batch vials in another freeze-drying equipment of similar scale, the LyoStar® III lyophilizer (SP Scientific, Warminster, PA, USA) (30).…”
Section: Microfd® Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…Whether it is electric heating or steam heating, the cost is much lower. While heating the materials in the freeze-drying box, it is necessary to use the refrigeration unit to cool the cold trap of the freeze-drying machine at a low temperature, so as to freeze the water vapor generated in the heating sublimation process, maintain the vacuum in the freeze-drying machine, and maintain the vacuum conditions for the continuous sublimation of ice crystals [18,19]. While the refrigeration unit cools the cold trap, it also needs to discharge the heat of the refrigeration unit to the outside through the condenser and absorber.…”
Section: Utilization Status Of Condensation Heat In the Refrigeration System Of A Vacuum Freeze-dryermentioning
confidence: 99%
“…[8][9][10][11] At the end of the process, a typical freeze-dried product has a low RM, even lower than 1%, 10,12 but a wide distribution of RM values can be found in the vials of the same batch. 13 In fact, pressure gradients between shelves, 14 non-uniformity of temperature of shelf surface, 15 and different heat fluxes to the vials according to their position in the dryer 16,17 are responsible of non-uniform pressure and temperature conditions in the drying chamber, particularly in large scale equipment. 14 As a consequence, taking also into account non-uniform nucleation temperature, 18 sublimation rate and product temperature are different from sample to sample 19 and, thus, the RM.…”
Section: Introductionmentioning
confidence: 99%